Ours, all ours. (Economist, 2013)
The article discusses the online gaming industry in China, with information on the growth of Chinese Internet transactions and platforms as of 2013. Topics include the regulation of online games to increase usage of Chinese products, the duplication of several Western Internet platforms and games by Chinese companies, and the decision of Internet search company Google to withdraw from China due to state-led hacking attempts.